2016
DOI: 10.3847/2041-8205/822/2/l27
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Three Pulsating, Mixed-Atmosphere, Extremely Low-Mass White Dwarf Precursors*

Abstract: We report the discovery of pulsations in three mixed-atmosphere, extremely low-mass white dwarf (ELM WD, M 0.3 M ⊙ ) precursors. Following the recent discoveries of pulsations in both ELM and pre-ELM WDs, we targeted pre-ELM WDs with mixed H/He atmospheres with high-speed photometry. We find significant optical variability in all three observed targets with periods in the range 320-590 s, consistent in time-scale with theoretical predictions of p-mode pulsations in mixed-atmosphere ≈ 0.18 M ⊙ He-core pre-ELM W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 28 publications
3
68
0
Order By: Relevance
“…Multi-periodic pulsations with periods comparable to those found in WASP 0247−25B and WASP 1628+10B have also been discovered recently in three other ELM proto-WDs (Gianninas et al 2016) 4 . Those belong to more frequent single-lined binary systems consisting of an essentially invisible primary, presumed to be a normal CO-core WD, and of an ELM proto-WD as the secondary.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Multi-periodic pulsations with periods comparable to those found in WASP 0247−25B and WASP 1628+10B have also been discovered recently in three other ELM proto-WDs (Gianninas et al 2016) 4 . Those belong to more frequent single-lined binary systems consisting of an essentially invisible primary, presumed to be a normal CO-core WD, and of an ELM proto-WD as the secondary.…”
Section: Introductionmentioning
confidence: 84%
“…2015;Córsico et al 2016;Gianninas et al 2016). In this context, Gianninas et al (2016) provided the first empirical evidence that pulsations in ELM proto-WDs can only occur if a significant amount of He is present in the atmosphere and, by extension, in the driving region.…”
Section: Introductionmentioning
confidence: 99%
“…Objects with constraints on a lack of pulsations from time series photometry are marked with × symbols (this work; Hermes et al 2012aHermes et al , 2013a. Pulsating pre-ELM WDs from Maxted et al (2013Maxted et al ( , 2014; Corti et al (2016) and Gianninas et al (2016) are marked with orange narrow diamonds. Typical log g ∼ 8 ZZ Ceti pulsators from Gianninas et al (2011), corrected for 3D convection effects (Tremblay et al 2013), are marked with yellow triangles.…”
Section: Discussionmentioning
confidence: 99%
“…Corti et al (2016) reported on two variable stars that occupy a region of parameter space where they could plausibly be either pre-ELM WD or SX Phoenicis pulsators. Finally, Gianninas et al (2016) discovered three pre-ELMs with mixed H/He atmospheres that pulsate at higher temperatures than an extrapolation of the empirical DA WD instability strip due to the presence of He in their atmospheres. have explored the properties of pre-ELM WD pulsations in the evolutionary models of Althaus et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…[23]- [27] found pulsations in eight of these ELMs, similar to the pulsations seen in DAVs (ZZ Ceti stars), as described in [29]. [30] found 17 pre-ELMs, i.e., helium-core white dwarf precursors, and [31,32] report pulsations in six of them. Pulsations are an important tool to study the stellar interior, and [33] - [37] report on theoretical models and pulsations of ELMs.…”
Section: Interacting Binariesmentioning
confidence: 62%